IJOER 2018
DOI: 10.18278/ijoer.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Infrastructure of Openness: Results from a Multi-Institutional Survey on OER Platforms

Abstract: The purpose of this study is to understand how higher education institutions are selecting and using technology platforms for the creation and delivery of Open Educational Resources (OER). A survey about OER technology was sent to various higher education institutions, resulting in 33 responses. The results suggest that institutions are most commonly using existing tools like the Learning Management System (LMS) to deliver OER, however third-party courseware also has a strong presence. The results also suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Publishing platforms are often an integral part of OER publishing programs in academic libraries, and the availability of such infrastructure contributes to the sustainability of a program (Essmiller et al, 2019). In a survey of 33 US higher education institutions, Nyland (2019) found that word processing tools were the most common technology used by faculty to author their own open textbooks, followed by the learning management system (LMS), Pressbooks and Web authoring tools, such as WordPress. Many examples of OER publishing programs found in the literature use Pressbooks as the publishing platform provided by the institution (Fisher, 2020;McGrath, 2018;Ross et al, 2018) or provided in collaboration with partners such as the Rebus Community (Batchelor, 2018;Smith, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Publishing platforms are often an integral part of OER publishing programs in academic libraries, and the availability of such infrastructure contributes to the sustainability of a program (Essmiller et al, 2019). In a survey of 33 US higher education institutions, Nyland (2019) found that word processing tools were the most common technology used by faculty to author their own open textbooks, followed by the learning management system (LMS), Pressbooks and Web authoring tools, such as WordPress. Many examples of OER publishing programs found in the literature use Pressbooks as the publishing platform provided by the institution (Fisher, 2020;McGrath, 2018;Ross et al, 2018) or provided in collaboration with partners such as the Rebus Community (Batchelor, 2018;Smith, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Quality of OER While OER brings tremendous benefits to educators and students, there have been many controversial discussions about the quality of OER, especially when OER were first introduced to educational institutions. Institutional stakeholders have concerns that OER adoption may result in lower quality or outcomes (Nyland, 2018). Research regarding student learning outcomes by students using OER and commercial textbooks have varied results.…”
Section: Controversies Surrounding Oermentioning
confidence: 99%
“…As the use of OER continues to grow, publishers are experiencing a decline in the sale of textbooks, and college textbooks use has been declining in recent years (Rosen, 2019). for technologies and services that help deliver the content (Nyland, 2018). Locking down OER in a closed platform caused controversial discussions related to the stewardship and use of OER.…”
Section: Controversies About Affordable Resources Provided By Publishersmentioning
confidence: 99%